2019
DOI: 10.1080/10942912.2019.1698603
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the differences of flavor profiles between two types of soy sauce by heat-treatment

Abstract: The difference of flavor profiles and physicochemical properties between the two types of raw soy sauces and heated soy sauces were investigated in the present research. The results indicated that no significant changes of physicochemical properties, organic acids (except succinic acid) or CIELAB color space among the samples after heat-treatment were observed. However, the content of volatiles was increased by about 30.89% in the fortified sample (PP1) by heat-treatment. The contents of 26 and 15 constituents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Then, for soy sauce samples of 4 days koji starter treatment showed that they have higher a* and b* color value than 3 days and 4 days tempeh mold treatment, which means the color of soy sauce samples with 4 days koji starter treatment were redder and more yellowish than 3 days and 4 days tempeh mold treatment. The color of soy sauce samples was majorly contributed by high amounts of maillard reaction products, including melanoidins that were formed during thermal treatment and fermentation process [10]. Maillard reaction is a reaction that occurs between an amino group of free amino, peptide chain residue or protein with the carbonyl group of a carbohydrate, this happens if both are heated or stored for a long time, while melanoidins are formed mainly from carbohydrates, phenolic compounds [11].…”
Section: Resultsmentioning
confidence: 99%
“…Then, for soy sauce samples of 4 days koji starter treatment showed that they have higher a* and b* color value than 3 days and 4 days tempeh mold treatment, which means the color of soy sauce samples with 4 days koji starter treatment were redder and more yellowish than 3 days and 4 days tempeh mold treatment. The color of soy sauce samples was majorly contributed by high amounts of maillard reaction products, including melanoidins that were formed during thermal treatment and fermentation process [10]. Maillard reaction is a reaction that occurs between an amino group of free amino, peptide chain residue or protein with the carbonyl group of a carbohydrate, this happens if both are heated or stored for a long time, while melanoidins are formed mainly from carbohydrates, phenolic compounds [11].…”
Section: Resultsmentioning
confidence: 99%
“…This is because these enzymes break starch, protein and fats down into their individual components [60]. Yet, taste aspects can also be redesigned when products containing A. oryzae are further treated through, e.g., specific heat treatments [61]. Because this study aimed to assess the use of A. oryzae after minimal processing, this process was not performed.…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…To the best of our knowledge, 2,3-dihydrobenzofuran has not been described neither in other maize-based foods nor cereal breads and was not detected in maize flours, so it was originated during the bread making process, similar to other furan derivatives [14][15][16]. This compound has been described in wines and soy sauce as a product of the Maillard reaction [82,83] and is associated with musky notes [55].…”
Section: Broas' Sensory Analysis and Volatile Compositionmentioning
confidence: 99%